Understanding Euler's Formula through Electrical Device - Pundeer, Purnima Singh (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
ICT integration is to use ICT to introduce, reinforce, supplement and extend skills.  It stimulates and motivates students, provides comfortable learning aids to understand the difficult concepts and processes It caters to different learning styles and helps students to gain knowledge of new technologies. Teaching modern techniques and technologies to the students enhances their creativity and innovation to develop tools to find solution of daily life problems. These type of activities increase the interests of the students in the class and break the monotony and boredom of the topics. The knowledge of robotics provides them not only a tool to give shape to their imagination but also the knowledge of advance technologies at this young age. As a part of Practical introduction to Robotics students watched some videos of robotics based equipments during Environment Awareness classes. These videos depicted the innovative methods developed by some students (other) and professionals to overcome some or the other daily life problems. Teacher found some of the students interested and enthusiastic to develop such type of instruments. That‘s why the basics of robotics were introduced and hands on experiences were given of bread board circuits, software, coding, AI, programming and inserting artificial minds for desired output by the devices. A study was conducted through questionnaire to observe the learning outcome of these technical activities which showed that 70% of the students were very much enthusiastic about the techniques, out of which 60% of them were able to understand the basics of the technology and 40% were able to develop such devices which include – soil humidity testing device, smoke detector, water level indicator etc.